Nanofibers: Click Synthesis, Aggregation‐Induced Emission and Chirality, Circularly Polarized Luminescence, and Helical Self‐Assembly of a Leucine‐Containing Silole (Small 47/2016). Issue 47 (December 2016) - Li, Hongkun; Xue, Shan; Su, Huimin; Shen, Bo; Cheng, Zhihui; Lam, Jacky W. Y.; Wong, Kam Sing; Wu, Hongkai; Li, Bing Shi; Tang, Ben Zhong
Abstract : The synthesis of a chiral fluorescent silole derivative containing l‐leucine methyl ester moiety (Silole–Leu) is reported by B. S. Li, B. Z. Tang, co‐workers on page 6593. Silole–Leu exhibits aggregation‐induced emission and circular dichroism, and circular polarized luminescence. Silole–Leu is endowed with the ability to self‐assemble into nano/micro helical luminescent fibers and their dimensions can be tuned by adjusting the ratio and volume of the mixed solvents for assembling.